Is antenatal depression associated with adverse obstetric and perinatal outcomes?. (18th March 2016) - Yedid Sion, Maayan; Harlev, Avi; Weintraub, Adi Y.; Sergienko, Ruslan; Sheiner, Eyal
Abstract: Objective : To examine whether a pre-gestational diagnosis of depression is a risk factor for adverse obstetric and neonatal outcome. Study design : A retrospective cohort study investigating maternal characteristics, obstetrical and perinatal outcomes in singleton pregnancies of women with and without a diagnosis of depression was conducted. A pre-gestational diagnosis of depression was made by a psychiatrist or family physician and was recorded in the patients' chart. Multiple logistic regression models were used to control for possible confounders. Results : During the study period, 256 312 deliveries occurred. Of which, 221 women (0.1%) had a pre-gestational diagnosis of depression. When examining obstetric outcomes, women with a diagnosis of depression were older (32.05 ± 5.772 versus 28.56 ± 5.851) and smokers (7.2% versus 1.1%), had a higher rate of preterm deliveries (37.99 ± 2.989 versus 39.02 ± 2.249) and cesarean sections (CS; 28.5% versus 13.6%) in comparison to the control group. When examining neonatal outcomes, neonates of women diagnosed with depression had a lower birth mean weight (3.038.47 ± 649.6 versus 3183.44 ± 551.8) and increased rates of perinatal mortality (3.2% versus 1.3%). Using a multiple logistic regression model, with perinatal mortality as the outcome variable to control for cofounders such as maternal age, preterm birth, chronic hypertension and gestational diabetes mellitus, a diagnosis of depression was not found to be an independent risk factor for perinatal mortality. Another multiple logistic regression model found advanced maternal age, smoking, preterm birth and labor induction to be associated with a diagnosis of depression. Conclusion : Pregnant women diagnosed with depression are at an increased risk for preterm birth, low birth weight, and CSs. However, it was not associated with increased rates of perinatal mortality.